Indução de resistência em batata inglesa e seu efeito sobre coleópteros desfolhadores e predadores - Assis, Franscinely Aparecida de (2010)
The South American Rootworm, Diabrotica speciosa (Germar, 1824) (Coleoptera: Chrysomelidae), is the key pest of the English potato culture because it causes economic damage due to the injuries their larvae cause to the tubers. The objective of this work was to evaluate the effects of silicic acid, acibenzolar-s-methyl (ASM) and diatomaceous earth (DE) application in English potato on defoliator and predator coleopterons and the possible effects on the vegetative development and the culture productivity. In laboratory a completely randomized design was adopted with three treatments and eight repetitions, being: 1 - control; 2 - sprinkled DE (0.5g/vase) and 3 - 1% sprayed DE. The potato plants, cv. Emeraude, were sprinkled or sprayed with DE 30 days after the planting and 24 hours after the application, the plants were supplied the insects, with and without a chance of choice. There was no significant difference among the treatments in relation to the number of leaflets/vase, however a lower leaflet with injury percentage was observed in plants that received the application of DE. Regarding the insecticide action of DE, its effect was verified after 48 hours. In the field experiment a casualized block design was used with four treatments and six repetitions, being: 1 - control; 2 - foliar spraying of 1% silicic acid; 3 - foliar spraying of 0.02% acibenzolar-s-methyl (ASM) and 4 - foliar spraying of 1.15% diatomaceous earth (DE). The application of the treatments did not influence the presence of defoliator and predator coleopterons in the culture, in the aerial part and in the soil, however the plants treated with silicic acid and/or DE were less attacked by the defoliators. Furthermore, the plants treated with acibenzolar-s-methyl or DE produced tubers with smaller number of injuries (holes). The spraying with silicic acid, ASM and/or DE also provided significant increase in the height and diameter of the plants, without, however, affecting the productivity. As a result, the resistance inductors tested can be recommended for the management of defoliator coleopterons in English potato as a complement to chemical control.